Comprehensive comparative morphology and developmental staging of final instar larvae toward metamorphosis in the insect order Odonata - Genta Okude (Nature Portfolio, 2021)
Abstract The order Odonata (dragonflies and damselflies) is among the most ancestral groups of winged insects with drastic morphological changes upon metamorphosis, and thus important for understanding evo-devo aspects of insects. However, basic developmental descriptions of Odonata have been scarce. In an attempt to establish the foundation of developmental and experimental biology of Odonata, we present an unprecedentedly comprehensive survey of dragonflies and damselflies, in total 158 larvae representing 49 species and 14 families, wherein morphological changes of all the final and/or penultimate instar larvae were photographed and monitored everyday. Although their morphology and development were diverse, we consistently identified two visually recognizable morphogenetic events in the final larval instar, namely start of wing expansion and onset of melanization on the wing sheaths, thereby categorizing the final instar into three stages. While the duration of the first stage ranged 4–66 days across diverse Odonata species, the second or third stages exhibited relatively small variation ranging 3–22 days or 1–8 days, respectively, probably reflecting the steady and irreversible metamorphosis process after stage 2. We also described other characteristic morphological changes during the larval development, although they were observed only in some Odonata species and lineages.